The Western Curriculum and Identity Conflict among Pakistani Students - Abdullah, Tauqeer; Ali, Johar (UI Scholars Hub, 2026)
Education systems play a critical role in shaping students’ cultural identities in an increasingly globalized world. In Pakistan, the growing presence of international schools following Western curricula exposes students to values that often diverge from local traditions. Drawing on Erikson’s identity theory, Berry’s acculturation model, and Tajfel and Turner’s social identity theory, this study examines how Western curricula influence students’ self-perception, identity conflict, and cultural alienation. Data were collected from 324 students (179 males, 145 females) enrolled in O-level and A-level programs across five international schools in Lahore, Punjab, using a cross-sectional survey design. The results indicate that Western curricula significantly shape the self-concept of students, frequently generating identity conflict and feelings of cultural alienation as local traditions and indigenous knowledge are marginalized. While such education enhances global competitiveness, it simultaneously fosters socio-cultural dissonance, undermining the sense of belonging of students. These findings highlight the need for curriculum reforms that balance global perspectives with indigenous cultural integration.